1976
DOI: 10.1136/jcp.29.2.154
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of four techniques for the routine diagnosis of Trichomonas vaginalis infection.

Abstract: SYNOPSIS Specimens from 495 patients attending Johannesburg hospitals and family planning clinics were examined for Trichomonas vaginalis by microscopy of Giemsa (GS), Papanicolaou (Pap), and acridine-orange (AO) stained smears, and by culture in Feinberg-Whittington medium. Culture, Pap and GS stained smears from vaginal swabs yielded fewer positives than AO stained smears. Although Pap-stained cytological smears gave the highest number of posit,ves, in 300% of these cases the presence of T.vaginalis could no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
1

Year Published

1979
1979
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 15 publications
2
31
1
Order By: Relevance
“…This is in agreement with a previously done study which showed that the infection rate detected by acridine orange staining was higher than either culture or other vaginal swab examinations [19]. Although acridine orange staining is easy to perform, rapid and screening of the vaginal smears is done in less time, the major disadvantage of this technique is that it requires special microscopic facilities, trained personnel and availability of the dye.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…This is in agreement with a previously done study which showed that the infection rate detected by acridine orange staining was higher than either culture or other vaginal swab examinations [19]. Although acridine orange staining is easy to perform, rapid and screening of the vaginal smears is done in less time, the major disadvantage of this technique is that it requires special microscopic facilities, trained personnel and availability of the dye.…”
Section: Discussionsupporting
confidence: 79%
“…Studies done by different workers have reported varying range of sensitivity (41-56%) of giemsa stained smears for the diagnosis of Trichomonas vaginalis infection [19,24,25]. In one study it was reported that giemsa staining had high sensitivity (100%) and specificity (99.69%) compared to culture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Most common symptoms associated are thin green colored discharge with pH >5, Discharge was malodoured and Vulval itching was the found to be associated commonly. Findings of our study was consistent with the reports of S R Fule et al, Madhivanan P et al, and Mason P R et al [23][24][25] These differences in variation may be due to variations in personal hygiene, environment and socio economic conditions which vary from place to place.…”
supporting
confidence: 83%
“…A very high prevalence of TV 47% was reported (28) . Studies have indicated it as reemerging pathogen and found to correlate with age.…”
Section: Ijmmmentioning
confidence: 99%